Comparison of ultrasound-guided subtransverse process interligamentary plane block with paravertebral block for postoperative analgesia in thoracic surgery: protocol for a randomised non-inferiority trial - Yang Liu; Hong Shi; Danyang Wang; Tianyi Zhu; Wenxin He (BMJ Open)
Introduction The subtransverse process interligamentary (STIL) plane block is an emerging interfascial plane block that has garnered attention for its potential to provide effective postoperative analgesia for breast and thoracic surgeries. However, a direct comparative assessment between the STIL plane block and the paravertebral block is currently lacking. Consequently, our study aims to assess the analgesic efficacy of the STIL block in comparison to paravertebral block for patients undergoing video-assisted thoracoscopic surgery (VATS).Methods and analysis This study is a randomised, parallel-controlled, double-blind, non-inferiority trial, with the goal of enrolling 114 participants scheduled for uniportal VATS at Shanghai Pulmonary Hospital. Participants will be randomly assigned in a 1:1 ratio through block randomisation to receive either the STIL plane block (n=57) or the paravertebral block (n=57). The primary outcome of the study is the area under the curve of Numerical Rating Scale(NRS) scores recorded over a 48-hour period following the surgical procedure. Secondary outcomes encompass the evaluation of Quality of Recovery-40, cumulative sufentanil consumption, serum inflammatory factors, rescue medication usage, the incidence of adverse events and the patient satisfaction scores.Ethics and dissemination This study has received approval from the Medical Ethics Committee of Shanghai Pulmonary Hospital (approval no. L22-329). Written informed consent will be obtained from all participants. The findings will be submitted for publication in peer-reviewed journals.Trial registration number ChiCTR2200066909.